2012
DOI: 10.1002/jmv.23221
|View full text |Cite
|
Sign up to set email alerts
|

The 40–80 nt region in the 5′‐NCR of genome is a critical target for inactivating poliovirus by chlorine dioxide

Abstract: Chemical disinfection is the most common method used to inactivate viruses from drinking water throughout the world. In this study, cell culture, ELISA, RT-PCR, and spot hybridization were employed to investigate the mechanism underlying chlorine dioxide (ClO(2) )-induced inactivation of Poliovirus type 1 (PV1), which was also confirmed by recombinant viral genome RNA infection models. The results suggested that ClO(2) inactivated PV1 primarily by disrupting the 5'-non-coding region (5'-NCR) of the PV1 genome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
16
0
5
Order By: Relevance
“…However, siRNAs that targeted the 5′-UTR of picornavirus failed to reduce virus replication29, whereas Pelletier et al found that a combination of two synthetic siRNAs targeting both the 5′-UTR and the 3D polymerase of PV was more effective and persistent than a single siRNA6. Additionally, in our previous study, we found that the PV 5′-UTR was a critical region for its disinfection by chlorine dioxide30. Interestingly, in the present study, we found that a specific siRNA, targeting the region between nucleotides 100–125 of the PV 5′-UTR strongly inhibited viroplasm formation in the context of PV infection and blocked PV-induced cell killing in virally infected Vero and A549 cells.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, siRNAs that targeted the 5′-UTR of picornavirus failed to reduce virus replication29, whereas Pelletier et al found that a combination of two synthetic siRNAs targeting both the 5′-UTR and the 3D polymerase of PV was more effective and persistent than a single siRNA6. Additionally, in our previous study, we found that the PV 5′-UTR was a critical region for its disinfection by chlorine dioxide30. Interestingly, in the present study, we found that a specific siRNA, targeting the region between nucleotides 100–125 of the PV 5′-UTR strongly inhibited viroplasm formation in the context of PV infection and blocked PV-induced cell killing in virally infected Vero and A549 cells.…”
Section: Discussionmentioning
confidence: 79%
“…The 5′-UTR has six stem-loop domains, representing two functional elements: (1) Domain I is the 1–80 nt region that forms a cloverleaf structure and is associated with the replication of viral nucleic acids. (2) Domains II–VI, in the 130–610 nt region, are associated with the synthesis of viral proteins6253031. In view of the fact that the specific siRNA-100 target sequence is located between nucleotides 100–125, which itself falls between Domains I and II, we hypothesized that this may help to prevent the stem-loop secondary structures from shielding the viral target RNAs access to the RNAi machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the inactivation mechanism of hepatitis A virus (a picornavirus) by ClO 2 was due to the loss of the 5= untranslated region of the genome and/or receptor-binding domain destruction on the capsid (53). It was also found that ClO 2 inactivated poliovirus, another picornavirus, primarily by disrupting a 40-to 80-nucleotide sequence in the 5=-noncoding region of the genome (54). On the other hand, working with bacteriophage MS2, it was found that the primary inactivation action of ClO 2 is viral protein degradation, not damage to the viral genome (55).…”
Section: Discussionmentioning
confidence: 99%
“…Genome alterations can also be induced. Some authors have suggested for chlorine dioxide that certain areas of the genome are more sensitive than others and are degraded differently (Simonet and Gantzer 2006;Jin et al 2012). These mechanisms could partially explain the underestimation induced by RT-qPCR approaches targeting short genome sequences compared to infectivity tests on bacteria or cell cultures for determining the inactivation of bacteriophages or viruses after exposure to disinfectants Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%